Effect of the counseling program and Ya Dok Khao herbal candy used on smoking reduction and cessation among people at Ban Khok Hua Chang sub-district health promoting hospital in Buriram Province - Suttipun, Nipar; Yuakthaisong, Jandee; Phanomrat, Arisara (Thai Journal of Nursing, 2025)
This quasi-experimental research aimed to compare health literacy on smoking, smoking cessation behaviors, the number of cigarettes smoked per day, and nicotine dependence before and after participating in the counseling program and Ya Dok Khao herbal candy used among people at Ban Khok Hua Chang sub-district health promoting hospital in Buriram Province. A sample of 30 participants was purposively selected. The research instruments included a counseling program and Ya Dok Khao herbal candy used and a questionnaire on health literacy on smoking, smoking cessation behaviors, the number of cigarettes smoked per day, and the level of nicotine dependence. Data were analyzed using descriptive statistics and t - test. The study results revealed that after participating in the counseling program and Ya Dok Khao herbal candy used, the participants had significantly higher mean scores of health literacy on smoking and smoking cessation behaviors than before the program participation. Additionally, the mean number of cigarettes smoked per day and the level of nicotine dependence were significantly lower than before the program participation at p < .05.